Tonsillitis and its Homoeopathic Approach (Homoeopathy for All, 2025)
The most prevalent illness in children  between the ages of two to fifteen is  tonsillitis. Recurrent tonsillitis can  result from multiple acute attacks  of the disease each year or from an  acute attack that occurs just once a  year. In children, this may result in  more serious issues. When treating  both acute and recurrent episodes of  tonsillitis, homoeopathic treatment  works better. Three essential  requirements for a The most prevalent illness in children  between the ages of two to fifteen is  tonsillitis. Recurrent tonsillitis can  result from multiple acute attacks  of the disease each year or from an  acute attack that occurs just once a  year. In children, this may result in  more serious issues. When treating  both acute and recurrent episodes of  tonsillitis, homoeopathic treatment  works better. Three essential  requirements for a homoeopath are  remedy, potency, and dose to treat  the acute state of tonsillitis and  manage repeated bouts.  are  remedy, potency, and dose to treat  the acute state of tonsillitis and  manage repeated bouts.
Keywords: remedy; potency